A compact broadband coplanar waveguide fed circularly polarized printed monopole antenna with asymmetric modified ground plane. Issue 7 (28th February 2020) - Alsariera, Hussein; Zakaria, Zahriladha; Awang Md Isa, Azmi; Alahnomi, Rammah; Mabrok, Mussa; Ahmed, Sharif; Alani, Sameer
Abstract: In this communication, a broadband circularly polarized (CP) monopole antenna with coplanar waveguide (CPW) feeding is proposed. It consists of a modified rectangular monopole, an asymmetric ground plane, a two‐linked inverted L‐shaped strips on the left CPW ground, and two rectangular horizontal slots in asymmetric CPW ground plane. The overall dimension is only 0.47λ o × 0.47λ o . The antenna prototype has been fabricated. The measured results indicate that a broad −10 dB impedance bandwidth (IBW) of 107.5% (4.3 GHz, 1.85‐6.15 GHz) and a broad 3 dB axial ratio ARBW of 104.3% (4 GHz, 1.855‐5.9 GHz) can be achieved; the average realized gain is 2.3 dBi for the entire CP band. The proposed antenna is an attractive candidate for several wireless communication systems.